Wind generated fluctuations in water mass structure in the Nordic Seas - Blindheim, Johan (ICES, 1999)
Hydroyaphic sections in the Nordic Seas which have been repeated during the 1990s are compared with observations from 1958 (IGY) in the Norwegian Sea and from 1965 in the Greenland Sea. The comparison shows that the water mass structure has changed considerably since 1958/1965. In the Greenland Sea there has been a warming since the 1970s and the volume of water with salinity higher then 34,9 has increased while the volume of older Greenland Sea Deep Water has decreased and vanished after 1995. The product of the vvinter convection when no deep water is formed, is a less dense water mass which spreads isopycnally on top of the deep water. Depending on wind conditions, thls water mass extends from the Greenland and Iceland Seas into the Norwegian and Lofoten basins and forms an intermediate layer between the inflowing Atlantic Water and the Deep water. Also the deep water formation seems to be wind generared since there seems to be close correlation between the upper layer salinity in the central Greenland Sea and the gradient of the mean sea level pressure across the East Greenland Current.